Pillars of Performance Improvement of Bawaslu Sidenreng Rappang Through Budget Accountability and Transparency - A Wahyuni; Syahriyah Semaun; Muzdalifah Muhammadun; Damirah Damirah; Andi Ayu Frihatni (Universitas Muhammadiyah Makassar, 2025)
This study aims to analyze the effect of accountability and transparency on the performance of Bawaslu Sidrap in managing the 2024 election budget. The research employs a quantitative descriptive approach with an associative design. The population includes all employees of Bawaslu Sidenreng Rappang Regency involved in the 2024 general election, and data were collected through questionnaires distributed via Google Forms. The results indicate that accountability achieved 77%, transparency 74%, and performance 74%, exceeding the expected value of 65%. Correlation analysis demonstrates that both accountability (X1) and transparency (X2) have a strong and significant relationship with Bawaslu performance (Y), with Pearson correlation coefficients of 0.679 and 0.722, respectively. The t-test shows that accountability significantly influences performance (p = 0.028 < 0.05), whereas transparency does not show a significant effect (p = 0.62 > 0.05). The F-test results confirm that accountability and transparency simultaneously have a significant effect on performance, suggesting that the variables complement each other when assessed together. These findings underscore the importance of strengthening accountability mechanisms to enhance Bawaslu’s effectiveness in managing election budgets. Although transparency supports good governance, its independent effect on performance is limited. Therefore, integrated strategies focusing on accountability improvement are essential to optimize institutional performance and ensure credible and efficient budget management.